Exploring Self-Concept as A Career Determinant for Students of Islamic Education Counseling Guidance Study Program: Study on BKPI IAIN Students Curup Semester VI Year 2021/2022 - Rizal, Syamsul (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2023)
This research is a descriptive qualitative research. The tempat of this research is IAIN Curup, Rejang Lebong Regency. The subject of the study was a student of BKPIconcentration semester VI. Data collection techniques by means of observation, interviews, documentation. Data analysis techniques by means of data collection, data presentation, and conclusions. From the research, it can be seen that knowledge regarding self-concept is many research subjects. BK students' knowledge of their overall self-concept is still looking for their identity and potential, the expectations of BK PI students regarding careers are not all interested in education. Keywords: self-concept, career, BKPI